Lean Accounting to Reduce Lead Time in the Expenditure Cycle - Yuni Fitrantinah; Viska Anggraita (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study analyzes the causes of long payment lead times in the Accounts Payable (AP) process at PT XYZ, an oil distribution company, and suggests improvements based on Lean Accounting principles. The company's vendor payment lead time target is 5 working days, but actual lead times range from 8 to 11.25 days, with only 44–63% of the target achieved. Key issues identified include redundant verification steps, delays in three-way matching (PO, GR, and invoices), and the reliance on physical documents that cause waiting and transportation waste. The process also faces delays due to approval queues, repetitive checks, and document errors requiring rework. Data was collected through interviews with key personnel, field observations, and document analysis. The root cause analysis revealed that the current process is based on a traditional accounting model, focusing on control through multiple manual checks instead of prevention and automation. The proposed Lean Accounting-based improvements include: (1) simplifying verification to a single control point with ERP system support, (2) reducing approval levels from six to three, with spot checks for supervisors, (3) adopting accounting by exception for high-value transactions and new vendors, (4) streamlining document processing to avoid batch waiting, (5) digitizing the process with a vendor portal, and (6) improving error prevention early in the process to reduce rework.